Two-stage amplification mechanism based on flexible hinge - WANG Xuecheng; ZHANG Shijun; CUI Xilong (Jixie chuandong)
ObjectiveA novel two-stage compound amplification mechanism design scheme was proposed in this study to address the friction and clearance issues inherent in traditional revolute pairs within the large stroke design of micro-displacement platforms.The aim is to achieve high-precision and significant stroke displacement amplification through structural innovation.MethodsUtilizing the theory of material mechanics, a static model was established. A two-stage compound amplification structure that integrates a flexible hinge lever amplification mechanics of materials with a bridge amplification mechanism was employed. Piezoelectric ceramics serve as the driving source, and a parameter optimization model was developed using Matlab software. The impact of key structural parameters on both the amplification ratio and input stiffness was systematically analyzed to identify the optimal parameter combination. The optimized structure underwent validation through multi-physical field simulation via finite element analysis.ResultsFollowing optimization, the mechanism attains an impressive displacement amplification ratio of 13.1 times, with its natural frequency reaching 92.3 Hz. The maximum discrepancies between theoretical calculations and simulation results are recorded at 2.4% and 3.5%, respectively, thereby demonstrating the feasibility of this structural design.